Correlation of the initial bone height to the middle facial height and the maxillary sinus volume: A Retrospective Study - BOU CHAAYA , Mark; MENASSA , Gabriel; GHOSN, Nabil; NICOLAS, Joyce; NAAMAN, Nada (International Arab Journal of Dentistry (IAJD), 2023)
This study aims to measure and establish a correlation between the initial bone height (IBH) at the dentate posterior maxillary sextants to the middle facial height (MFH) and the maxillary sinus volume (SV). Thirty CBCTs split evenly between males and females were retrospectively selected and processed to measure the SV and the IBH from the first premolar to the second molar. A clinical measurement was performed on each patient to evaluate the MFH. A significant positive correlation was found between MFH and SV. No significant correlation was found between the IBH of the first premolar and the SV or MFH on both sides. The results showed a significant negative correlation between the IBH of the other teeth examined and the SV on both sides. A significant negative correlation was found between the MFH and the IBH of the second premolar, first molar, and second molar of each side. It can be concluded that the maxillary SV increases with the MFH, and the IBH decreases when the SV and the MFH increase except for the first premolar. The clinical relevance of this study lies in the capability of the general practitioner to estimate the IBH in the posterior dentate maxilla by measuring the MFH. Patients with a risk of having a low IBH can be advised, in the case of an extracted tooth, to consider ridge preservation techniques or implant therapy as soon as possible to avoid future complex surgical interventions.